Quantum teaching learning model as solution to improve learning activity and mathematics learning outcome - Jayantika, I G A N T; Parmithi, N N; Dyanawati, N P A (Journal of physics. Conference series, 2019)
Most of students at X class MIA 1 Senior High School PGRI 4 Denpasar can not reach the minimum requirements criteria. It's caused of lack of attention of students on the learning process, and lack of collaboration of subject matter with student's reality life. One effort can be taken to improve learning activity and Mathematics learning outcome was by apply Quantum Teaching Learning Model. This study aims to improve learning activity and Mathematics learning outcome students. This study was a classroom action research conducted in 2 cycles with the subject of research was all of students at X class MIA 1 Senior High School PGRI 4 Denpasar Lesson 2017/2018 which consists of 46 students. The objects in this study was learning activity and Mathematics learning outcome. Learning activity data obtained by observation sheet while data of Mathematics learning outcome obtained by test technique. The result of this study concluded that quantum teaching learning model is a solution to improve learning activity and Mathematics learning outcome of students especially at X class MIA 1 Senior High School PGRI 4 Denpasar. Other school which have similar problem can apply this model to solve the problem.